2006
DOI: 10.1051/kmae:2006013
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Characterisation of Streams in Tuscany (Italy) for the Management of the Threatened Crayfish Austropotamobius Pallipes Complex

Abstract: Any initiative aimed at the management of a threatened species needs a good knowledge of its environmental requirements. Aims of this study were to individuate suitable areas for the reintroduction of crayfish species belonging to the Austropotamobius pallipes complex and to evaluate the causes of the local extinction in Tuscany (Italy) of some populations. Between May 2003 and September 2004, we collected ecological data from 19 streams of 4 catchments, 9 watercourses where crayfish were present (WI) and 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 45 publications
5
27
2
Order By: Relevance
“…Finally, our findings suggested that mortality in studied populations of A. pallipes is mainly due to natural causes (M=69% and 67% in males and females respectively), and only a portion is due to poaching. This result contrasts with data reported for Tuscany, where illegal fishing is one of the main causes of mortality for the species (Renai et al, 2006). All the studied populations are within European protected sites, Natura 2000.…”
Section: Discussioncontrasting
confidence: 94%
“…Finally, our findings suggested that mortality in studied populations of A. pallipes is mainly due to natural causes (M=69% and 67% in males and females respectively), and only a portion is due to poaching. This result contrasts with data reported for Tuscany, where illegal fishing is one of the main causes of mortality for the species (Renai et al, 2006). All the studied populations are within European protected sites, Natura 2000.…”
Section: Discussioncontrasting
confidence: 94%
“…Aphanomyces astaci; Gherardi and Holdich, 1999). Similarly to A. pallipes (Holdich and Reeve, 1991;Reynolds et al, 2002;but see Trouilhe´et al, 2006), Austropotamobius italicus is extremely sensitive to slight changes in environmental conditions, so that several authors classify it as a good bioindicator of water quality (Scalici and Gibertini, 2005;Renai et al, 2006). This study assessed the status of some populations of A. italicus in Central Italy by providing information about their size and structure.…”
Section: Introductionmentioning
confidence: 98%
“…For example, despite a growing acceptance that A. pallipes is not a strict bio-indicator of high water quality (Füreder and Reynolds, 2003), the heterogeneous nature of the habitat for crayfish must be maintained and enhanced, and water quality monitored in both rivers and lakes Renai et al, 2006). The bottom substrate and presence of morphological structures acting as hiding places, and the geographical isolation of the habitat seem to be of importance.…”
Section: > Suitability Of Target Habitatsmentioning
confidence: 99%